Nurturing wise spending habit among children: the role of parents - Mohd. Zain, Nor Razinah; Zakariyah, Habeebullah; Mahadi, Nur Farhah (2020)
Children are blessings bestowed to their parents within a family unit. Parents have huge responsibilities to educate, nurture, and love their children since they are the continuing generation of the Muslim Ummah. Financial education and planning are important to be educated by parents to their children. This is a knowledge that can help the children to avoid wastage of wealth and appreciate it as a part of Islamic wealth management. With such wealth, these children can contribute further to the society or at least to support themselves throughout their lives. The habit of wise spending can be nurtured to these children since their young age. Soon, the wise spending will be a habit and part of their lifestyle. Focusing on the notion of Hifz al-Mal and Islamic wealth management strategy, this research evaluates the roles of parents in nurturing the habit of their children for wise spending. By using mixed methods, This research investigates the trend of parents in educating wise spending habit to their children. A collection of data is collected by using online survey among Muslim parents at Gombak, Selangor, Malaysia. It is found that parents are committed to nurture their children with the wise spending habit. They do not mind to support their children’s lifestyle as long as it is appropriate with their living expenses and in compliance with Shariah.